PERAN WALI KELAS DAN PERHATIAN ORANGTUA DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI KELAS 5 UPT SPF SDN CENDRAWASIH I KOTA MAKASSAR - Rahmawati .; Nurdin .; Muhammad Fahreza W (STKIP Pembangunan Indonesia Makassar, 2022)
This study aims to find out: (1) the roles and responsibilities of the homeroom teacher, (2) the attention and responsibility of parents, (3) the collaborative efforts made by the homeroom teacher and parents in improving student achievement at UPT SPF SDN Cendrawasih I Makassar City and (4) Student achievement by holding collaboration between homeroom teachers and parents of students at UPT SPF SDN Cendrawasih I Makassar City. This research is a qualitative research with a Naturalistic Inquiry approach, namely how to observe and collect data in a natural setting. Then the data collection procedure through observation, interviews and documentation. The results of the study show that (1) the roles and responsibilities of homeroom teachers at UPT SPF SDN Cendrawasih I Makassar City as educators, teachers, motivators, facilitators and counselors can improve student achievement. (2) The attention and responsibility of parents towards students is more thorough than that of homeroom teachers because students spend more time at home than at school. (3) Collaborative efforts made by homeroom teachers and parents in improving student achievement at UPT SPF SDN Cendrawasih I Makassar City include: familiarizing and supervising students in the discipline of studying and worship time, always providing motivation to students, establishing mutual communication good, always inform the development of student achievement to parents. (4) Student achievement at UPT SPF SDN Cendrawasih I Makassar City by holding collaboration between homeroom teachers and parents, among others, increasing class wins obtained by students.Keywords: School Quality Improvement, Education Management Standards.Keywords: homeroom teacher, parental attention, learning achievement